A discussion on the renaming of Cymodocea serrulata to Oceana serrulata: implications for seagrass research and conservation in Vietnam - Luong, Cao Van; Nguyen, Manh Linh; Bui, Tuan Minh (Vietnam Journal of Marine Science and Technology, 2023)
The seagrass species previously classified as Cymodocea serrulata has been reclassified as Oceana serrulata. This reclassification is based on genetic analysis, which reveals a distinct separation of this species from others within the Cymodocea genus. This change will have implications for future research and taxonomy, highlighting the value of advanced genetic techniques in elucidating the relationships between seagrass species. Nevertheless, further analysis is warranted as new evidence emerges. The transition to the designation Oceana serrulata harmonizes traditional morphological descriptions with modern genetic phylogenetics, enabling a more precise classification. This adjustment will facilitate targeted research on the newly categorized Oceana genus’s biology, ecology, and conservation. We emphasize the importance of disseminating this update to inform the scientific community about these alterations in species classification. Accurate taxonomy serves as the essential foundation for biological research and conservation efforts. Presenting the rationale and process behind taxonomic changes enhances understanding of scientists’ challenges. Furthermore, evaluating name changes encourages scientific discourse and feedback, underscoring the significance of ongoing taxonomic reassessment in advancing seagrass biology and conservation.